Potential Detrimental Health and Social Effects of Ghosting - PETRIC, Domina (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
Ghosting, which is the unilateral termination of communication with a partner, is allegedly most frequently done using technology. Scholarly interest in the practice has increased recently. Ghosting is usually viewed as a novel relationship-breakup method since many academics attribute its prominence to media technology. This study revealed that ghosting is a frequent occurrence in the workplace and is not a new phenomenon. Historically, the emergence of depressive illnesses and job discrimination have been linked by several studies. However, the relationship between job discrimination and ghosting is rarely discussed in literature. This study investigates the possible negative health and social impacts of ghosting on both private and professional lives. First, this study used thematic analysis to explore the interpersonal theory of psychiatry, the relational self-concept, and ghosting as a social phenomenon. Ghosting in both private and professional contexts and its psychological effects were also covered. According to this study, getting ghosted can be incredibly painful and have a negative impact on one’s mental health and self-esteem. In addition, this paper argues that administrative silence at work and communication refusal by an employer can have detrimental financial, legal, and emotional effects on the party being ghosted. This paper makes a case for the necessity of tighter rules in the workplace that would control inter-personnel professional communication and make people legally compelled to give thorough responses to important questions. The methodology used for this study is the content and textual analysis of primary and secondary works of literature.